Human Resource Management In The Digital Era: Community Empowerment Program For Msmes In Tasikmalaya - Agoes Hari Edy Wibowo; Iwan Sugianto; Lati Sari Dewi; Siti Amirah Makarim; Fitriani; Agus Sopian; Risman Barkah (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
The digital era has transformed the way organizations manage their human resources, demanding adaptive skills, digital competencies, and agile systems. Micro, Small, and Medium Enterprises (MSMEs), especially in rural and semi-urban areas, often struggle to adapt to these rapid changes due to limited knowledge, technology access, and workforce readiness. This community service program aimed to enhance the human resource management (HRM) capacity of MSME actors in Tasikmalaya through digital literacy training, workforce planning, and the introduction of simple HR digital tools. Using the IPOO framework (Input–Process–Output–Outcome), the program was attended by 30 MSME owners and managers and facilitated by faculty members from STIE Latifah Mubarokiyah. Results showed increased understanding of HRM principles, improved ability to manage digital workforces, and enthusiasm to adopt digital tools for employee data and task tracking. This initiative underscores the importance of equipping MSMEs with modern HR skills to remain competitive and sustainable in the digital age.